62‐3: A 120Hz 1G1D 8k4k LCD with Oxide TFT. Issue 1 (29th May 2019) - Chang, ChiaMing; Tsai, ChiaHsiu; You, Jian-Jin; Lai, Wei; Chin, Tsung-Shou; Tseng, Hsien-Kai; Lin, Yuzuo; Wang, Hao Yu; Yeh, BoLiang; Wu, ChenChung; Teng, DeZhang; Chen, Chunlin; et al.
Abstract : We succeeded the true 1G1D 75" 8K4k LCD with Oxide thin‐film transistor (TFT) for the first time. The initial prototype TFT process was in Gen.6 FAB, but now, we have been developed mass producible back channel etching (BCE)‐type oxide TFT process in Gen.7 FAB. As its first application, 1.7μsec pixel chargeable 1G1D 120Hz 8‐domain LCD without any additional compensation part for image quality deterioration such as transmittance loss and color washout is introduced. In practical point of view, this technology can render about 20% reduction of total production material cost compare to a‐Si technology. Moreover, simplified 1G1D metal line structure can contribute to production yield improvement. In this report, we present the latest AUOs Oxide TFT backplane development.